Genetic Variants as Predictive Markers for Ototoxicity and Nephrotoxicity in Patients with Locally Advanced Head and Neck Cancer Treated with Cisplatin-Containing Chemoradiotherapy (The PRONE Study) - Driessen, Chantal M. (Cancers (Basel), 2019)
Ototoxicity and nephrotoxicity are potentially irreversible side effects of chemoradiotherapy with cisplatin in locally advanced head and neck cancer (LAHNC) patients. Several predictive genetic variants have been described, but as yet none in LAHNC patients. The aim of this study is to investigate genetic variants as predictors for ototoxicity and nephrotoxicity in LAHNC patients treated with cisplatin-containing chemoradiotherapy. Our prospective cohort of 92 patients was genotyped for 10 genetic variants and evaluated for their association with cisplatin-induced ototoxicity (ACYP2, COMT, TPMT and WFS1) and nephrotoxicity (OCT2, MATE and XPD). Ototoxicity was determined by patient-reported complaints as well as tone audiometrical assessments. Nephrotoxicity was defined as a decrease of ≥25% in creatinine clearance during treatment compared to baseline. A significant association was observed between carriership of the A allele for rs1872328 in the ACYP2 gene and cisplatin-induced clinically determined ototoxicity (p = 0.019), and not for ototoxicity measured by tone audiometrical assessments (p = 0.449). Carriership of a T allele for rs316019 in the OCT2 gene was significantly associated with nephrotoxicity at any time during chemoradiotherapy (p = 0.022), but not with nephrotoxicity at the end of the chemoradiotherapy. In conclusion, we showed prospectively that in LAHNC patients genetic variants in ACYP2 are significantly associated with clinically determined ototoxicity. Validation studies are necessary to prove the added value for individualized treatments plans in these patients.